2020
DOI: 10.3390/pathogens9110946
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Cryptosporidium in Bactrian Camels (Camelus bactrianus) in Xinjiang, Northwestern China

Abstract: Cryptosporidium species are ubiquitous enteric protozoan pathogens of vertebrates distributed worldwide. The purpose of this study was to gain insight into the zoonotic potential and genetic diversity of Cryptosporidium spp. in Bactrian camels in Xinjiang, northwestern China. A total of 476 fecal samples were collected from 16 collection sites in Xinjiang and screened for Cryptosporidium by PCR. The prevalence of Cryptosporidium was 7.6% (36/476). Six Cryptosporidium species, C. andersoni (n = 24), C. parvum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
20
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
7
20
2
Order By: Relevance
“…Our genotyping data revealed the presence of two Cryptosporidium species, including C. parvum (in two animals presenting with diarrhea) and C. bovis (in an asymptomatic animal). Cryptosporidium infections have been previously reported in diarrheic dromedary camels in Algeria ( 27 ) and Iran ( 48 ), whereas C. parvum has already been described in Egyptian dromedary camels ( 38 ); this is the first report of cattle-adapted C. bovis in this host species in the country and the third report globally after the description of the parasite in Bactrian camels in China ( 61 , 62 ). In Egypt, previous research has revealed the occurrence of C. bovis in cattle and buffalo populations ( 101 105 ).…”
Section: Discussionmentioning
confidence: 71%
“…Our genotyping data revealed the presence of two Cryptosporidium species, including C. parvum (in two animals presenting with diarrhea) and C. bovis (in an asymptomatic animal). Cryptosporidium infections have been previously reported in diarrheic dromedary camels in Algeria ( 27 ) and Iran ( 48 ), whereas C. parvum has already been described in Egyptian dromedary camels ( 38 ); this is the first report of cattle-adapted C. bovis in this host species in the country and the third report globally after the description of the parasite in Bactrian camels in China ( 61 , 62 ). In Egypt, previous research has revealed the occurrence of C. bovis in cattle and buffalo populations ( 101 105 ).…”
Section: Discussionmentioning
confidence: 71%
“…Cryptosporidium infection in camels has become an increasingly important source of zoonotic disease transmission to humans, especially in communities with poor sanitation and inadequate medical facilities [30]. In recent years, there have been many reports worldwide of camel infections caused by different Cryptosporidium species, including C. parvum, C. hominis, C. andersoni, C. occultus, C. bovis, C. ubiquitum, C. muris, Cryptosporidium rat genotype IV and camel genotypes [30][31][32][33][34]. In China, C. parvum, C. hominis, C. ubiquitum, C. occultus, C. bovis and C. andersoni have been found to be infecting camels [25,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been many reports worldwide of camel infections caused by different Cryptosporidium species, including C. parvum, C. hominis, C. andersoni, C. occultus, C. bovis, C. ubiquitum, C. muris, Cryptosporidium rat genotype IV and camel genotypes [30][31][32][33][34]. In China, C. parvum, C. hominis, C. ubiquitum, C. occultus, C. bovis and C. andersoni have been found to be infecting camels [25,34,35]. In this study, we first reported a C. muris isolate from Bactrian camels by sequence analyses and then verified its identity through infectivity and parasitic sites via experimental infection of laboratory animals.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this special issue also included molecular epidemiological studies directed to assess the occurrence, genetic diversity and zoonotic potential of Cryptosporidium spp. and G. duodenalis in pet dogs and cats [17], livestock [18], and farmed rabbits and rats [19][20][21], mostly in China.…”
mentioning
confidence: 99%
“…It should be noted that most molecular-based surveys conducted so far, failed to demonstrate zoonotic transmission events between pet dogs/cats and humans [40,41]. In another survey, Cao et al [18] assessed the occurrence and molecular diversity of Cryptosporidium spp. in faecal samples (n = 476) from Bactrian camels in the Xinjiang Uygur Autonomous Region.…”
mentioning
confidence: 99%